Comprehensive Experimental Investigation of Operational Parameter Sensitivity in Proton Exchange Membrane Fuel Cell Performance - Renhua Feng; Zhanye Hua; Jing Yu; Shaoyang Wang; Laihua Shi; Xing Shu; Ziyi Yan; Jiayi Guo (Batteries)
In this study, the sensitivity of operating parameters such as the hydrogen and air excess coefficient, cathode inlet pressure, intake relative humidity, and coolant inlet temperature and their effects on the performance of single proton exchange membrane fuel cells (PEMFCs) are experimentally assessed. The results revealed that the fuel cell node voltage increases as the hydrogen and air excess coefficient increases, and the impact of the hydrogen and air excess coefficient on the fuel cell node voltage gradually increases as the current density increases. However, a higher hydrogen and air excess coefficient is not always better. The node voltage increases as the intake pressure increases. However, it is not that a higher intake pressure is always better, but rather that there is an optimal intake pressure value to achieve the best overall performance of the fuel cell. The node voltage increases as the coolant inlet temperature increases at most fuel cell current densities. However, the optimum fuel cell operating inlet temperature is not necessarily higher, as the coolant inlet temperature may have a strong coupling relationship with other operating conditions that will also affect the fuel cell performance. The fuel cell operating inlet temperature may have a strong coupling relationship with the intake relative humidity, and both of these parameters must be well-matched to achieve better fuel cell performance.